From school to scene: subjugated knowledges and teh informal education of queer young men in Vancover, Canada and Sydney, Australia - Egan, John P. (Canadian Journal for the Study of Adult Education, 2008)
Abstract This ethnographic study examines the experiences of young queer men becoming queer adults. Twenty-seven gay-, bi-, or queer-identified, same-sex attracted men from Sydney and Vancouver, from diverse cultural and educational backgrounds, describe tacit, informal learning experiences acquired through seeking queer community. These men bring into adulthood scars and wounds from K–12 school environments rife with homophobia; when they begin exploring queer community through their local Scene, their expectations of finding comfort, support, and validation are inevitably met with disappointment. Until society at large accepts its queer members as full and equal citizens — regardless of age — queer young men will continue to spend a significant amount of their early adulthood overcoming their formative years. Résumé Cette étude ethnographique examine l’expérience des jeunes hommes queers devenus des adultes queers. Vingt-sept gai, bisexuelle ou queer identifié, même sexe attire de Sydney et Vancouver, des milieux culturels et éducatifs divers, décrivent des expériences d’études tacites et informelles acquises en cherchant la communauté étrange. Ces hommes introduisent dans des cicatrices et des blessures d’âge adulte des environnements scolaires K-12 nombreux avec la homophobie; quand ils commencent à explorer la communauté queer par leur Scène locale, leurs espérances d’y trouver le confort, l’appui et la validation sont inévitablement rencontrées avec désenchantement. Jusqu’à la société en générale accepte ses membres queer en tant que pleins et égaux citoyens-sans se soucier de jeunes hommes queers continueront à dépenser une quantité significative de leur âge adulte tôt surmontant leurs années formatives.